Máquina de Calibración y Análisis de Características de Sensores de Temperatura - Purtscher, Norberto; Verdezoto, Gabriela; Mosquera, Gustavo; Oña, Omar Oña (Revista Ciências Exatas, 2016)
To calibrate an instrument or pattern need another instrument to provide more accurate than the real value is to be used for comparison with the indication of the instrument under calibration. The focus of this project is to develop a tool for laboratory practice in the area of instrumentation to satisfy academic requirements in further training for the Career of Mechatronics Engineering, Technical University of the North. The purpose of this work is to design and implement a machine for calibration of resistive sensors, testing its static and dynamic characteristics. The calibration machine consists of four systems: a liquid bath oil to provide a constant temperature environment where you can test the working demo sensor while calibrating thermometers, a certified digital thermometer pattern which have a real reference variable to measure conditioning system for each type of temperature sensor and a human machine interface through which control of the machine and to generate data.